Does AI Respect Patient Autonomy? Navigating the Ethical Tensions in Digital Health - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The rapid integration of Artificial Intelligence AI into healthcare promises revolutionary improvements in diagnostics, treatment planning, and administrativ...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Clinical Decision Support; Medical Ethics